Literature Review Metode Penilaian Sisa Umur Heat Recovery Steam Genearator (HRSG) Berdasarkan Standar American Society Of Mechanical Engineers (ASME) - Priambada, Danang; Winarto, Felixtianus Eko Wismo (LPPM Universitas Pekalongan, 2025)
The role of power plants is crucial in supporting various sectors, particularly in oil and gas exploration. One of the key components, the Heat Recovery Steam Generator (HRSG), plays a vital role in combined cycle power plants. However, as HRSG operates, several risks arise, such as performance degradation due to factors like corrosion, fouling, and thermal fatigue. This review aims to analyze studies conducted in Indonesia on the remaining life assessment methods of HRSG based on the American Society of Mechanical Engineers (ASME) standards. The literature review was conducted by collecting and analyzing references from ASME standards through national journals found via Google Scholar, published between 2018 and 2024. The data includes the methods and analyses used in the remaining life assessment of HRSG. The assessment methods for HRSG remaining life include corrosion rate calculation, stress rupture testing using the Larson-Miller Parameter (PLM), material degradation analysis, the Risk-Based Inspection (RBI) approach, as well as pipe thickness evaluation and allowable working pressure assessment. There is no single method that can comprehensively provide an effective HRSG remaining life assessment. Each method has its own advantages and limitations. Keywords: Heat Recovery Steam Generator, remaining life assessment, ASME standards, corrosion, Risk-Based Inspection, Larson-Miller Parameter.